Working Paper 41: Targeting unexplained wealth in British Columbia: An analysis of Recommendation 101 of the Final Report of the Commission of Inquiry into Money Laundering in British Columbia (Basel Institute on Governance Working Papers, 2022)
The final recommendation of the Commission of Inquiry into Money Laundering in British Columbia (‘the Commission’) urged the government to legislate an unexplained wealth order (‘UWO’) as part of a wider approach to counter the prevalence of money laundering and proceeds of crime in the province.This document analyses the feasibility of this recommendation. It:• briefly explains the concept of unexplained wealth and how it can be targeted through legislative instruments;• outlines the reasons for which the Commissioner proposed a UWO for British Columbia;• explains how a UK-style UWO works and assess the probability that a mechanism of this kind would successfully recover unexplained wealth in British Columbia; • addresses the constitutional issues that may arise if a UK-style UWO was introduced, as outlined by former Supreme Court Justice, the Honourable Thomas A. Cromwell C.C., in his annexed opinion to the report;• explains other legislative options that target unexplained wealth (including those in Western Australia and Ireland) and assess their constitutional compatibility and potential effectiveness as compared to a UK-style UWO;• explores the legal rights issues that may arise if either a UK-style UWO or a traditional UWO was introduced; and• outlines the legislative safeguards that could be put in place to reduce the risk that any such mechanisms would negatively impact on established legal rights.This document has been prepared by experts working with the Basel Institute on Governance, an independent not-for-profit organisation dedicated to countering corruption and other financial crimes, and the Vancouver Anti-Corruption Institute, an organisation devoted to anti-corruption efforts and legislative change.